OECD-project 'The role of qualification systems in promoting life long learning' : country report: the Netherlands - Hövels, Ben [Verfasser]; Kraayvanger, Geert [Mitarbeiter]; Roelofs, Mariska [Mitarbeiter] (Knowledge Centre for Vocational Training & Labour Market, 2004)
"This country-report is part of the OECD-Project 'The role of qualification systems in promoting life long learning'. It offers an overview of the main characteristics of the qualifications system in the Netherlands as far as of relevance for life long learning, especially focussing on upper secondary vocational education and training (VET). Our main conclusion is that the VET-qualification system in the Netherlands in principle do have many ingredients for promoting life long learning, especially due to both its objectives and structural characteristics." (Publisher, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; I 2.2.1 Westeuropa; Berufliche Qualifikation; Berufsbildungssystem; Lebenslanges Lernen; Niederlande